Evaluasi Penyerapan Anggaran Sebagai Indikator Kinerja Pelaksanaan Anggaran : (Studi Kasus Balai Monitor Spektrum Frekuensi Radio Kelas I Bandung) - Anggia Nur Nazma (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The effective implementation of the State Budget must be supported by the implementation of quality and good spending. To accelerate development and encourage economic growth, a planned budget absorption process is needed that has a significant impact on the flow of the national economy. To achieve this goal, ideally, budget absorption must be even and proportional throughout the fiscal year. With the issue of the end of every fiscal year, namely uneven budget absorption, this study aims to evaluate budget absorption for consideration to improve budget implementation performance. This research was conducted with passive participatory observation, in-depth interviews and supporting data used annual performance reports and detailed budget absorption indicators from OM SPAN. This study reveals that the budget absorption at the Bandung Class 1 SFR Monitor Center is not proportional and unevenly quarterly, even though every year it has a high IKPA value. This is due to invalid budget planning, varied human resource capabilities, weak internal communication, and technically there is a difference between the SPM submission and the issuance of SP2D. With this research, it is hoped that the work unit can increase and improve budget absorption that is more valid and accurate.